Identification of Novel Histone Deacetylase 6‐Selective Inhibitors Bearing 3, 3, 3‐Trifluorolactic Amide (TFLAM) Motif as a Zinc Binding Group. (9th July 2021) - Kurohara, Takashi; Tanaka, Keita; Takahashi, Daisuke; Ueda, Satoshi; Yamashita, Yasunobu; Takada, Yuri; Takeshima, Hirokazu; Yu, Shengwang; Itoh, Yukihiro; Hase, Koji; Suzuki, Takayoshi
Abstract: Pharmacological inhibition of histone deacetylase 6 (HDAC6) is an effective therapeutic strategy for cancer and immunological diseases. Most of the previously reported HDAC6 inhibitors have a hydroxamate group as a zinc binding group (ZBG), which coordinates to the catalytic zinc ion of HDAC6. The hydroxamate group is liable to metabolically generate mutagenetic hydroxylamine; therefore, non‐hydroxamate HDAC6 inhibitors would be advantageous. In this study, to identify novel non‐hydroxamate HDAC6‐selective inhibitors, screening of a chemical library and the subsequent structural optimization were performed, which led to the identification of HDAC6‐selective inhibitors with 3, 3, 3‐trifluorolactic amide (TFLAM) as a novel ZBG. The identified inhibitor showed potent and selective HDAC6‐inhibitory activity in cells and induced regulatory T (Treg) cell differentiation. Abstract : Non‐hydroxamate HDAC6‐selective inhibitors : We identified isoindoline compounds bearing 3, 3, 3‐trifluorolactic amide (TFLAM) as a novel zinc binding group by screening a compound library and the subsequent structure‐based drug design (SBDD). The identified inhibitor exhibited potent and selective HDAC6‐inhibitory activity in cells and induced Treg cell differentiation.